Brave : the junior novelization - Trimble, Irene (New York : Random House, 2012)
Princess Merida, a skilled archer, accidently unleashes a curse on the kingdom, and, on her journey to set things right, she learns about bravery.
5.9
3-6
3-6
700
Keywords: Princesses -- Juvenile fiction; Sex role -- Juvenile fiction; Princesses -- Fiction; Sex role -- Fiction; Princesses -- Fiction; Gender role -- Fiction; Scotland -- History -- Juvenile fiction; Scotland -- History -- Fiction; Scotland -- History -- Fiction